EFEKTIFITAS THERAPI MUROTTAL TERHADAP POLA TIDUR BAYI BBLR - Putriana, Yeyen; Aliyanto, Warjidin (MIDWIFERY JOURNAL, 2021)
Background :Babies with low birth weight (LBW) are at high risk for health problems. LBW infants require special handling to minimize the risk of infant morbidity and mortality. The latest complementary treatments for LBW are Kangaroo Method Treatment (KMT), baby massage and murottal therapy. The murottal effect on LBW is the increase in body weight and the baby's body temperature becomes stable. The weight gain in this study is thought to be a mechanism of long quiet sleep in LBW infants.Purpose:This study aims to determine sleep patterns through morottal therapy as one of the stimulations in LBW care along with Kangaroo Method Treatment (KMT).Methods :The research design used quasi experimental with pretest control group design . The research was conducted at Abdul Moeloek Hospital (RSUAM) Bandar Lampung. The population in this study were all LBW infants who were treated in the Perinatology Room of the General Hospital. Sampling technique using probability sampling. The sample size was determined using the two-mean difference hypothesis test formula, obtained as many as 30 samples.Results : showed that there was a difference in the increase in sleep duration on days I, 2, 3 and 4 in the intervention group (60 minutes of murottal therapy and control (30 minutes of morottal therapy).Conclusion:The conclusion is that there are differences in sleep patterns in the intervention group (60 minutes) and the control group (30 minutes) with a v palue of 0.000. among the babies low birth weight at Abdul Moeloek Hospital (RSUAM) Bandar LampungSuggestion: This study recommends the use of murottal therapy in the treatment of LBW for 60 minutes a day. Keywords: LBW, KMT, Sleep Pattern, Murottal Therapy AbstrakLatar Belakang : Bayi dengan berat badan lahir rendah (BBLR)  berisiko tinggi mengalami masalah kesehatan. Bayi BBLR membutuhkan penanganan khusus guna memperkecil risiko kesakitan dan kematian bayi. Perawatan komplementer  BBLR terkini adalah Perawatan Metode Kangguru (PMK), pijat bayi dan therapi murottal. Pengaruh murottal terhadap BBLR adalah adanya kenaikan berat badan dan suhu tubuh bayi menjadi stabil. Kenaikan berat badan pada penelitian tersebut diduga adanya mekanisme tidur tenang yang Panjang pada bayi BBLR.Tujuan :Penelitian ini bertujuan mengetahui pola tidur melalui therapi morottal sebagai salah satu stimulasi dalam perawatan BBLR bersamaan dengan Perawatan Metode Kangguru (PMK) .Metode :Desain penelitian menggunakan quasi experimental dengan pretest control group design . penelitian  dilaksanakan di rumah sakit Abdul Moeloek (RSUAM) Bandar Lampung. Populasi dalam penelitian ini adalah seluruh bayi BBLR yang dirawat di Ruang Perinatologi  RSUAM. Tehnik pengambilan sample menggunakan probalility sampling. Besar sample ditetapkan menggunakan rumus uji hiptesis beda dua mean berpasangan didapatkan sebanyak 30 sample.Hasil : terdapat perbedaan peningkatan lama tidur pada hari ke I, 2, 3 dan 4 pada kelompok intervensi (60 menit therapi murottal dan control (30 menit therapi morottal).Kesimpulan terdapat perbedaan pola tidur pada kelompok intervensi (60 menit) dan kelompok control (30 menit) dengan v palue 0,000. Pada bayi BBLR di RSUAM Bandar LmapungSaran : therapi murottal dapat diberikan selama 60 menit kepada bayi BBLR untuk meningkatkan pola tidurnya Kata kunci : BBLR, PMK, Pola Tidur,  Therapi Murottal